Avaliação do efeito da adição de raízes na erodibilidade de um solo arenoso - Venturini, Jéssica Anversa (2019)
The practice of introducing the use of vegetation in engineering works, for centuries, is used to strengthen the soil, protect and reduce erosion processes. However, a large part of the studies is devoted to investigating the efficiency of above-ground vegetation, few evaluate the impact of roots on erosion rates control. The presence of natural fibers (roots) tends to increase the surface roughness and soil permeability, increasing water infiltration and decreasing surface outflow and erosive potential. The combination of this component with engineering works is called Soil Bioengineering. In this sense, the present research has as main objective to evaluate the effect of the presence of roots in the erodibility of a sandy soil of alluvial origin, located in the district of Vale Vêneto, city of São João do Polêsine in the state of Rio Grande do Sul. In order to reach the proposed objectives, direct (Inderbitzen) and indirect erodible evaluation tests (laboratory cone, disintegration, infiltrability and loss of mass by immersion) were carried out with undisturbed, remolded without roots and remolded with roots at three different rates (0,5%, 1,0% and 1,5%) samples. The roots were originated from the emerald grass (Zoysia japonica Steud). Tests of chemical, physical and mineralogical characterization of the material under study were also carried out. The results obtained through laboratory cone tests showed that as the number of roots in the test specimens increased, the penetration values in the saturated samples increased. In the condition of natural moisture, the specimens became more resistant, reducing the values of penetration. The disintegration test showed a high susceptibility to erosion for remolded samples regardless of root rate. In the tests that comprised the MCT methodology, there was a decrease in mass loss values while the root rate increased. For the values of sorption coefficient the amount of roots was not an influence factor in the conditions of natural and pre-moistened humidity. The direct evaluation, performed through the Inderbitzen tests, confirmed that soil loss is generally proportional to ramp inclination and test flow rate. When comparing the remolded samples without roots with the samples remolded with 1,5% of roots in the condition of natural humidity, the erodibility rate presented a decrease of 38,99%. In the condition of dry air humidity this number reached 79,84%, being even more expressive in the condition of pre-moistened humidity where the erodibility rate reached a fall of 90,44%.